The Involvement of Turkish Women in the Pre-Genocide Turkish Propaganda about Smyrna and the Implementation of the Genocidal Policy, 1919-1922 - Mirzoyan, Elina Z.; Martoyan, Tehmine R. (The Historical Review/La Revue Historique, 2025)
After the armistice of Mudros, rallies, gatherings and protests were organised across Turkey, with the active participation of Turkish women and men. The landing of Greek troops in Smyrna on 15 may 1919 became a reason, or, rather, a pretext, for Turkish women to initiate and participate in the outdoor rallies. These rallies, organised as a “struggle against the occupation” of Smyrna, started in the squares and districts of cities and gradually became large-scale throughout Turkey. To organise and control this process, Mustafa Kemal (as of 1934, Atatürk) initiated several organisations and associations, and issued the Havza Circular. Kemal legalised the persecution and abuse of Christians. Turkey attempted to liberate itself from international obligations and responsibility by breaching international laws and contracts. The annihilation of Smyrna’s Armenians and Greeks and the arson of their districts was the continuation of the genocidal policy of the Young Turks.